Peningkatan Kapasitas Aparatur Pemerintah Daerah dalam Perencanaan Pembangunan (Studi Kasus di lingkungan Pemerintah Kota Probolinggo) - Wahju Krisnanto; Nany Suryawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Giving greater authority to local governments to carry out development innovations in the era of regional autonomy is both an opportunity and a challenge. The granting of such authority requires the support of the capacity of the regional government apparatus to be able to plan innovative development program activities based on the needs of the region. In fact, there are still many local government apparatus that do not yet have the capacity to plan innovative development program activities. Data information is needed to determine the factors that become the root cause of the low capacity of local government officials to carry out development planning. The purpose of knowing the root factor that causes the low capacity of government apparatus in carrying out development planning is to obtain solutions that can be done by local governments to increase the capacity of their government apparatus. As a research location, Probolinggo City was chosen. The method used in this study uses a qualitative descriptive approach. The results of the study revealed that there were several factors causing the low capacity of the regional government apparatus, the evaluation mechanism was not effective, there was no documentation and communication of the results of development program activities, lack of Human Resources development plans, weak development program of input data planning and the rapid mutation intensity of bureaucratic apparatus.